ARTIFICIAL INTELLIGENCE: ANALYSIS OF VARIOUS AGENT PROGRAMMING LANGUAGES - Poonam Priyanka Patra; Dr. Prakash Kumar Pathak (International Journal For Research In Advanced Computer Science And Engineering, 2024)
Artificial Intelligence is one of the emerging areas of computer science which provides different methods or technologies that can be used to improve the efficiency of existing systems and make them more users friendly. Intelligent Agent is one of the AI technology that had tremendous potential. In this paper, we analyse the various programming languages emerged for the development of Intelligent Agent.